Koleksi Quran Di Pusat Manuskrip Narathiwat: Isu-Isu Perolehan Dan Pemuliharaan - Syed Najihuddin Syed Hassan; Abdulloh Salaeh; Nidzamuddin Zakaria; Amran Abdul Halim; Norhasnira Ibrahim; Ma Yu Long (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
THE 6TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2019/ EDITED BY : DR. NURULWAHIDAH FAUZI DR. SAMER NAJEH ABDULLAH SAMARH DR. MESBAHUL HOQUE DR. TAZUL ISLAM “AL QURAN RAHMATAN LIL A’LAMIN: VISION AND CHALLENGES” 8th – 9th October 2019 / 9 – 10 Safar 1441H Hosted By : Faculty Of Quranic And Sunnah Studies, Universiti Sains Islam Malaysia (USIM)